Marketing Strategy of Mrs. Luqi's Processed Salted Egg Products in the Perspective of Islamic Business Ethics in Sidoarjo Regency - Farisi, Nashirul Haq Al; Suryaningsih, Sri Abidah (Formosa Journal of Applied Sciences, 2025)
This study examines the marketing strategy of salted egg products by Mrs. Luqi in Sidoarjo Regency in the perspective of Islamic business ethics. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results showed that the marketing strategy carried out includes aspects of product, price, place, promotion, human resources, process, and physical evidence (7P). This strategy is good enough to fulfill the principles of Islamic business ethics, although there are still obstacles such as the lack of understanding of digital-based marketing and the process of checking product quality. This article recommends increasing understanding of digital technology and maintaining product quality to support business sustainability.